2006
DOI: 10.1002/uog.2645
|View full text |Cite
|
Sign up to set email alerts
|

Velamentous cord insertion into the lower third of the uterus is associated with intrapartum fetal heart rate abnormalities

Abstract: Objectives

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(61 citation statements)
references
References 17 publications
(16 reference statements)
1
55
1
4
Order By: Relevance
“…Other authors report a sensitivity of 62.5% in antenatal detection of velamentous insertion of the cord, with a positive predictive value of 100% and a negative predictive value of 99.6%. 18 According to Lee et al, vasa praevia can be identified from the second trimester of pregnancy. 19 Nevertheless, given that some cases of vasa praevia resolve themselves spontaneously at the end of the pregnancy, they consider it reasonable to confirm the diagnosis in the third trimester, when its detection has the greatest impact on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Other authors report a sensitivity of 62.5% in antenatal detection of velamentous insertion of the cord, with a positive predictive value of 100% and a negative predictive value of 99.6%. 18 According to Lee et al, vasa praevia can be identified from the second trimester of pregnancy. 19 Nevertheless, given that some cases of vasa praevia resolve themselves spontaneously at the end of the pregnancy, they consider it reasonable to confirm the diagnosis in the third trimester, when its detection has the greatest impact on treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The lower uterine segment has insufficient decidual formation and elongated by extension of the uterine isthmus as gestation advances. Cases of velamentous cord insertion located on the lower uterine segment was closely associated with a very high rate of non-reassuring fetal status and should be considered analogous to vasa previa [12,13] . Vasa previa and velamentous cord insertion located on the lower uterine segment may be associated with extension of the lower uterine segment and atrophy of the chorion villosum that covers the lower segment of the uterus.…”
Section: Discussionmentioning
confidence: 99%
“…Sepulveda 4 subsequently reported a 100% success rate in identifying cord insertion site at 11 to 14 weeks ultrasound scan in 533 cases with only 30 s added to the overall time. At 18 to 20 weeks scan in 3,446 pregnancies by general obstetricians and gynecologists with and without additional color Doppler, Hasegawa et al 5 reported 62.5% sensitivity of antenatal detection of velamentous cord insertion with 100% positive predictive value and 99.6% negative predictive value. Although we perform obstetric ultrasound in nearly all of our patients, only a minority of sonographers look for the site of cord insertion in the placenta.…”
Section: Discussionmentioning
confidence: 99%